Relationship between food neophoia and motivation towards consuming local food among foreign tourists in Melaka, Malaysia - Alias, Amirah (2016)
Malaysian tourism industry is growing steadily over the years as evident by theincreasing number of tourist arrivals and receipts. Among the services and products involve in tourism are food and beverage, which has substantial role not only as a basic need for the tourists‘ physiology but also to enhance their xperience. One of the important issues for food producers and marketers is to understand the tourists‘ food choice. Hence, this study was conducted with the main purpose to identify the food related personality (food neophobia group) and tourists‘ motivation to consume local food since these factors could influence food choice and consumption at a destination.The study was guided by the conceptual framework of factors influencing tourist food consumption in a destination. Motivational factors and food related personality are suggested as factors from the tourists. The motivations were identified and categorized into 5 dimensions namely culture experience, excitement, interpersonal, sensory appeal and health concern. As for the food neophobia group, it was determined by using Food Neophobic Scale. Most of the analysis used was mean analysis. It was found that cultural motivation is the motivation to consume local food particularly tasting local food in its traditional setting. In order to identify the food neophobic group, respondents are categorized into low, medium and high neophobia groups based on their score. Cluster analysis was used in order to determine the membership for each group.ii In this study, most of respondents‘ ages between 18 to 33 are in the medium neohpobia group (with score between 21 to 30). Profiles of these identified categories were further developed based on their socio-demographic and media habits. The findings provide an understanding for foreign tourists‘ motivation to consume Malaysian local food and food neophobia groups that can predict their food consumption at the destination. This information is essential for the food producers and marketers to promote local food to be prime choice among foreign tourists while visiting Malaysia.